ANALYSIS OF INSIDER TRADING PRACTICE RELATING TO LAW PROTECTION EFFORT FOR MINORITY SHAREHOLDERS - Muryanto, Yudho Taruno; Widyoningrum, Riezdiani Restu (Yustisia, 2018)
This article aims to describe the characteristics of insider trading according to the Act No. 8 of 1995 on Capital Market and the implication with legal effort that can be taken by minority shareholder. The characteristics of insider trading according to the act No 8 of 1995 on Capital Market are in line with fiduciary duty theory principle, there is involvement of insider by the misappropriation trusted. Insider trading has impacts to the other investors, especially to minority shareholder. The difference opportunity to do transaction causes financial disadantages, and for the loss, minority shareholder can doing legal effort, submit their civil lawsuit to the insider trader.